Problematika Pendidikan Islam pada Generasi Digital Native: Telaah terhadap Akhlak, Literasi Keagamaan, dan Pembelajaran Berbasis Teknologi - Surma Hayani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
he rapid development of digital technology has significantly transformed educational systems, including Islamic education. Digital native generations, who were born and raised in a digital environment, possess distinct learning characteristics, behaviors, and educational needs compared to previous generations. This study aims to examine the challenges of Islamic education among digital native students by focusing on morality, religious literacy, and technology-based learning. A quantitative survey approach was employed in this study. The population consisted of 236 students enrolled in Integrated Islamic Elementary Schools (SDIT) in Pekanbaru, all of whom were selected as research participants through a total sampling technique. Data were collected using questionnaires and analyzed through descriptive statistics and multiple linear regression using SPSS software. The findings reveal that students demonstrated high levels of morality, religious literacy, and technology-based learning engagement. Regression analysis indicated that morality, religious literacy, and technology-based learning significantly influenced Islamic education challenges, both partially and simultaneously. Morality emerged as the most dominant predictor. These findings suggest that Islamic education in the digital era requires the integration of character development, religious literacy enhancement, and technology utilization grounded in Islamic values. This study contributes to the development of an adaptive Islamic education model capable of responding to digital transformation while preserving students’ moral and spiritual foundations..